2012
DOI: 10.1136/tobaccocontrol-2011-050248
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tobacco control policies on smoking prevalence and smoking-attributable deaths in Ireland using theIrelandSSsimulation model

Abstract: Predictions from the IrelandSS model suggest that policies implemented between 1998 and 2010 have had considerable effect; however, appreciable reductions in smoking prevalence and SADs can still be achieved through increasing taxes, maintaining a high-intensity tobacco control media campaign, introducing graphic health warnings and improving smoking cessation services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 13 publications
0
29
0
1
Order By: Relevance
“…2,22,23 The SimSmoke model has been validated for four states of the United States of America and more than 20 countries. [5][6][7][12][13][14][15][16][17][18][19][20]23,24 Table 1 summarizes policies and effect sizes based on expert panels and published literature reviews. 23 We provide upper and lower bounds for effect sizes based on variability estimates from our previous work.…”
Section: Effect Size Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…2,22,23 The SimSmoke model has been validated for four states of the United States of America and more than 20 countries. [5][6][7][12][13][14][15][16][17][18][19][20]23,24 Table 1 summarizes policies and effect sizes based on expert panels and published literature reviews. 23 We provide upper and lower bounds for effect sizes based on variability estimates from our previous work.…”
Section: Effect Size Parametersmentioning
confidence: 99%
“…[1][2][3][4] Since their introduction, countries have steadily implemented recommended MPOWER policies. Early leaders in adopting rigorous MPOWER measures include Brazil, 5 Ireland 6 and Thailand. 7 As the movement to adopt MPOWER policies gains momentum, more countries have passed laws and many others have put advocacy efforts in place to support legislation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the deaths occurred in middle age (35-69yrs) and on average, approximately 22 years of life are lost by those killed in middle age by smoking Despite being the first country in the world to introduce a comprehensive smoke free workplace legislation and having one of the highest tobacco product prices in the world, Ireland has a sizable adult smoking prevalence of 19.5% 3 . Previous research has found that improvement in smoking cessation and increased resource allocation to media campaigns are the highest priority for Ireland's tobacco control interventions at present 4 . While measures have been implemented to discourage people from smoking initiation, attention must also be given to smoking cessation in order to achieve an appreciable reduction in smoking related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The ambition to reduce figures of such proportions has been motivating groups of researchers who have smoking as their object of study. While it may be a global trend to do research in the line of "factors associated with the rates of interruption of the smoking habit" 1,5,6 and the effect of public policies on tobacco control 1,7,8 , base research focusing on the knowledge of associations between smoking and its users' health impairments remains relevant and current.…”
mentioning
confidence: 99%